ETIKA BERMEDIA DALAM PERSPEKTIF DAKWAH ISLAM: KAJIAN PUSTAKA TENTANG HOAKS DAN CYBERBULLYING - Ismatillah, Laila; Salma Adawiah, Hanifah; Azizah Putri, Amalia; Suryandari, Meity (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of social media in Indonesia has brought about significant changes in public communication patterns. However, behind this convenience, negative phenomena have emerged in the form of the spread of hoaxes and increasingly worrying cyberbullying behavior. Based on data from the Ministry of Communication and Information Technology, there were 1,923 hoaxes detected throughout 2024, while cyberbullying cases had exceeded 4,000 by mid-2023. This study aims to analyze how the Islamic da'wah perspective can serve as an ethical basis for using media to address the phenomenon of hoaxes and cyberbullying in the digital space. This study used a library research method with a descriptive qualitative approach. Data were obtained through documentation techniques from primary sources, including the Quran, hadith, and academic books, as well as secondary sources consisting of scientific journal articles indexed in Sinta and Scopus published between 2019 and 2024. Data analysis was conducted using content analysis and thematic analysis techniques, while data validity was ensured through source triangulation. The results of this study indicate that Islam has a comprehensive ethical framework for communication, encompassing the principle of tabayyun (verifying information) in Surah Al-Hujurat verse 6, as well as the prohibition on mocking and insulting others in Surah Al-Hujurat verse 11, both of which are highly relevant as normative solutions to hoaxes and cyberbullying. Islamic da'wah plays a strategic role in shaping the moral awareness of social media users through the internalization of noble character values ​​in the digital space. This study contributes to enriching the academic literature on Islamic media ethics in Indonesia and recommends strengthening empathetic and solution-oriented digital da'wah programs based on Quranic values.